ANALISIS PERBEDAAN RETURN DAN RISK SAHAM ANTARA SAHAM SYARIAH DAN SAHAM KONVENSIONAL PADA MASA PANDEMI COVID-19 DI INDONESIA (STUDI PADA PERUSAHAAN LQ45) - Rufaidah, Sz; Arfan, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the differences in return and risk between sharia stocks and conventional stocks in LQ45 indexed companies during the Covid-19 pandemic. The sample of this research is company stocks indexed LQ45, of 45 stocks on the LQ45 index there are 24 observations sharia stocks (JII indexed) and 12 observations conventional stocks (not indexed JII). The type of data used is secondary data from the Indonesia Stock Exchange website. This study uses a quantitative approach with Independent Sample T-test as data analysis method, then the analysis is carried out using the SPSS application. The results revealed that there was no significant difference between the return and risk of sharia stocks and conventional stocks in companies indexed LQ45 during the Covid-19 pandemic.